2009
DOI: 10.2146/ajhp070392
|View full text |Cite|
|
Sign up to set email alerts
|

Methadone-associated Q-T interval prolongation and torsades de pointes

Abstract: Q-T interval prolongation and TdP associated with the use of methadone are potentially fatal adverse effects. A thorough patient history and ECG monitoring are essential for patients treated with this agent, and alterations in treatment options may be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 57 publications
1
75
0
2
Order By: Relevance
“…Extra caution is also warranted in situations that cause hypokalaemia such as diarrhoea or vomiting and use of diuretics. Pretreatment electrocardiogram (ECG) screening is recommended in such cases [11,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Extra caution is also warranted in situations that cause hypokalaemia such as diarrhoea or vomiting and use of diuretics. Pretreatment electrocardiogram (ECG) screening is recommended in such cases [11,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…28 A history of unexplained syncope or seizures should also be considered because these symptoms may reflect underlying cardiac problems which predispose to TdP. 29 Further, women appear to have a greater risk of developing methadone-induced TdP. In a literature review, Markar et al 30 found that about 70% of medicationinduced TdP cases involved women, irrespective of other risk factors.…”
Section: The Methadone-qtc-tdp Linkmentioning
confidence: 99%
“…1969-2002 m. aprašyti 59 tokie atvejai (29). Verpstinė skilvelių tachikardija gali progresuoti į skilvelių virpėjimą ir sąlygoti staigią mirtį (41,44). QT ilgėja dėl specifinės kalio kanalų blokados, ypač dėl uždelstos "lyginimo" kalio srovės greitai aktyvuojamo komponento selektyvios blokados (I kr ).…”
Section: Nepageidaujamas Metadono Poveikisunclassified
“…(idealu būtų stebėti 72 val.). Verpstinės skilvelių tachikardijos gydymui vartojamas magnio sulfatas, amjodaronas į veną (3,19,20,41).…”
Section: Gydymasunclassified